2009
DOI: 10.1080/17487870903314583
|View full text |Cite
|
Sign up to set email alerts
|

Growth effects of FDI in 80 developing economies: the role of policy reforms and institutional constraints

Abstract: Theoretical and empirical literatures have identified several channels through which foreign direct investment (FDI) influences economic growth. This paper examines the impact of FDI on economic output growth per worker using aggregate production function augmented with FDI inflows, economic policy reforms and institutional constraints. The paper covers 80 developing countries over the period 1980-2006. We use panel data and employ fixed, random effects and GMM methods for estimation. Our results highlight the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 24 publications
2
9
0
Order By: Relevance
“…Significant effects of institution quality on foreign direct investment and economic performance have been found in various studies (Vadlamannati and Tamazian, 2009, Okada and Samreth, 2014, Asamoah et al, 2016, Buchanan et al, 2012. By using data for 130 countries and regarding the role of corruption as an absorptive capacity (over the period of 1995 -2008), Okada and Samreth (2014) indicated that the direct effect of FDI on economic growth is insignificant, but the growth effect of foreign direct investment is strengthened when interacting with corruption control.…”
Section: The Relationship Between Fdi Trade and Growth: The Role Of mentioning
confidence: 98%
“…Significant effects of institution quality on foreign direct investment and economic performance have been found in various studies (Vadlamannati and Tamazian, 2009, Okada and Samreth, 2014, Asamoah et al, 2016, Buchanan et al, 2012. By using data for 130 countries and regarding the role of corruption as an absorptive capacity (over the period of 1995 -2008), Okada and Samreth (2014) indicated that the direct effect of FDI on economic growth is insignificant, but the growth effect of foreign direct investment is strengthened when interacting with corruption control.…”
Section: The Relationship Between Fdi Trade and Growth: The Role Of mentioning
confidence: 98%
“…Too strict foreign trade policy may also influence the attraction of FDI. High customs taxes can be sufficient motive for foreign companies to invest in production for local market, thus avoiding strict protective policy of the country (Vadlamannati & Tamazian, 2009;Cvetanović, Despotović & Mladenović, 2018).…”
Section: Foreign Direct Investmentsmentioning
confidence: 99%
“…Vadlamannati & Tamazian (2009) However, not all developing economies progress at the same rate (Schwab, 2010).…”
Section: Developing Economiesmentioning
confidence: 99%